IMPLEMENTASI KEBIJAKAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DI SDN 1 LASUSUA (MODEL GOGGIN) - Qhanita Wulandari Arif; Nurul Imana; Nuryanti Mustari (STKIP Subang, 2026)
This study aims to analyze the implementation of the School Operational Assistance (BOS) policy at SDN 1 Lasusua using Goggin’s Policy Implementation Model. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving the principal, BOS treasurer, and teachers. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings indicate that the content of the BOS policy has been well understood by policy implementers at the school level. Policy communication as an intervening variable has been carried out through socialization activities and school meetings; however, policy understanding has not been evenly distributed among all implementers. The implementation of BOS funds has positively contributed to school operational activities and the learning process. The implementation environment and implementers’ capacity generally support policy execution, although administrative constraints, limitations of the online reporting system, and delays in fund disbursement remain challenges. This study confirms that policy communication plays a strategic role in linking policy content and implementation outcomes and serves as a key factor in enhancing the effectiveness of BOS policy implementation in primary schools.